Bullying in film: reception analysis of "Pesbukers Comedy on Antv" - Syamsul Rijal; Maulana Iban Salda; Amirul Haq RD (Penerbit Universiti Kebangsaan Malaysia, 2023)
The study is based on moral argument issues about bullying on the television show Pesbukers episode 14 on March 1, 2019. There is a shift in value at the event where expressions of insult, harassment, intimidation, violation of social norms, and demeaning people are considered taboo, this event is considered a normal thing and even seems proud, cool, and trendy for someone who does it. The audience can give various meanings to the pesbukers TV program and be adapted it to their daily lives. The study aimed to describe the audience's reception of the bullying act at the Pesbukers event using Stuart Hall encoding-decoding reception analysis. This research uses descriptive qualitative research methods using Stuart Hall's reception analysis. Reception analysis will focus on the meeting between the text and the reader or in other words the media and audience. Reception analysis views the audience as producers of meaning who actively create meaning, not just as consumers of media content. The results showed that each informant was in three positions, dominant reading, negotiatedd reading, and oppositional reading. Dominant reading is dominated by children, negotiated reading is dominated by teenagers, and oppositional reading is dominated by parents/adults. Researchers found that these events by television comedy Pesbukers in the form of bullying, jokes, ridicule, drama, and entertainment can damage children's morale and mentality in their daily lives, both at school, a home, and playing because they are in the dominant reading position.